Critical Evaluation of Failed Maxillary Resin Bonded: A Case Study - Beh, Yew Hin; Ariffin, Azirrawani (UI Scholars Hub, 2022)
Resin bonded bridge (RBB) is a conservative, medium to long-term restoration of missing teeth. A high rate of debonding was the main limitation in a clinically demanding situation. Objective: To highlight the critical evaluation in identifying the contributing factors leading to the failure of RBBs and avoiding as well as controlling such factors optimally prior to providing further rehabilitative treatment. Case report: This case illustrates a young patient who received resin bonded bridges to replace her missing lateral incisors. Unfortunately, she had issues with bridge debonding, in which one of the abutment teeth was extracted due to caries under the retainer. The patient was then treated with multiple cantilever bridges to restore the missing dentition after optimising the risk factors. Conclusion: With an improved understanding and material advancement, RBB survival tends to be longer nowadays. As it was conservative, in the incidence of failure, other treatment options remain open. However, each failed case should undergo a critical evaluation of the failing aetiology and its mechanism to prevent future occurrences.